DETERMINANTS OF DEVELOPMENT OF INNOVATIONS IN THE INSURANCE BUSINESS (INNOVATIVE ECONOMY, 2020)
Czerniak J., Klapkiv L. DETERMINANTS OF DEVELOPMENT OF INNOVATIONS IN THE INSURANCE BUSINESS  Purpose. The aim of the article is to presentation the main factors of development of innovations in the world and Ukrainian insurance market. The solution of this goal involves identifying the factors influencing the development of innovations and conducting a qualitative analysis of the influence of the selected factors on the level of innovation of the insurance business.Methodology of research. Achieving the goal was based on general scientific methods of cognition. The method of analysis and observation is used to identify the factors of innovation activity in the insurance business, the method of systematization is used to group the main factors of the development of innovations in the insurance market, a graphical method - to visualize the results of the study.Findings. The external and internal factors of development of innovations in the insurance business are revealed and their qualitative analysis is carried out. The key sources of innovations in insurance are outlined: firstly, technological push and secondly, innovations caused by the features of the insurance market (market pull). In our opinion, it is also appropriate to break down the factors of demand and supply factors. It is noted that the need for implementation of innovative solutions is determined by two key features of insurance: the constant processing of large amounts of data and asymmetry of information, which may be a source of risk in insurance activities. A significant role of technological progress in solving the problem of asymmetry of information and improving the relationship with new generations of consumers of insurance services is noted.Originality. The selected determinants of innovation (in particular, asymmetry of information and generation change) in the insurance business are analyzed.Practical value. The research results can be taken into account when forming the strategy of development of the insurance market.Key words: Insurance companies; innovations; technological progress; asymmetry of information; generation.
Keywords: Key words; Insurance companies; innovations; technological progress; asymmetry of information; generation.